Bridging Tradition and Technology: A Sociotechnical Perspective on Digitalising the Kasongan Pottery Industry - Dino Rahmat Hidayat; Hakim, Lukman (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2025)
The fast growth of digital technology in Indonesia, with an estimated 221.6 million internet users (APJII, 2024), has pushed many business sectors to employ digital media to boost competitiveness and market reach. One of the businesses affected is the Kasongan pottery industry, which is noted for producing ceramics of significant cultural and artistic significance. This study will look into the notion of digitalisation management and the influence of digital adaption on ceramic entrepreneurs in Kasongan. This study employs a qualitative method using a case study methodology, which includes observation and in-depth interviews with business players. The study's findings suggest that Kasongan pottery entrepreneurs continue to experience challenges in embracing digital technologies. The key barriers are the delayed regeneration of business actors and poor digital literacy, which results in restricted usage of digital platforms for marketing and company administration. Generational transitions also result in disparities in mindsets and levels of technological adaptability, complicating conventional enterprises' digitalisation processes. The lack of awareness of digital marketing methods also poses a problem to boosting the industry's competitiveness. As a result, the government, universities, and the business community must work together to enhance digital literacy and expedite the adoption of technology in the Kasongan pottery sector in order for it to survive and thrive in the digital age. The key barriers are the delayed regeneration of business actors and poor digital literacy, which results in restricted usage of digital platforms for marketing and company administration. Generational transitions also result in disparities in mindsets and levels of technological adaptability, complicating conventional enterprises' digitalisation processes. As a result, the government, universities, and the business community must work together to enhance digital literacy and expedite the adoption of technology in the Kasongan pottery sector in order for it to survive and thrive in the digital age.